Research of Fragment Mechanism Security in IPv6 Network Protocol - Xianglin Wang; Chen Zhu; Dongmei Sun; Mingyue Li; Qingzi Shen (Dianxin kexue)
Based on open source Snort platform,the packet block mechanism in IPv6 network was discussed.The behavior using IPv6 packet fragment to attack network was studied.Against to the problems,such as too little for IPv6 packet segment,overlapping section and so on,it put forward the corresponding countermeasures.The intrusion detection system were designed and implemented for piecewise leak testing.The experiments show that the design of intrusion detection system can detect the abnormal IPv6 packet,and Snort to support for IPv6 function was improved and optimized.